Key protein-coding genes related to microglia in immune regulation and inflammatory response induced by epilepsy - Jing Cao (AIMS Press, 2021)
Several studies have shown a link between immunity, inflammatory processes, and epilepsy. Active neuroinflammation and marked immune cell infiltration occur in epilepsy of diverse etiologies. Microglia, as the first line of defense in the central nervous system, are the main effectors of neuroinflammatory processes. Discovery of new biomarkers associated with microglia activation after epileptogenesis indicates that targeting specific molecules may help control seizures. In this research, we used a combination of several bioinformatics approaches, including RNA sequencing, to explore differentially expressed genes (DEGs) in epileptic lesions and control samples, and to construct a protein-protein interaction (PPI) network for DEGs, which was examined utilizing plug-ins in Cytoscape software. Finally, we aimed to identify 10 hub genes in immune and inflammation-related sub-networks, which were subsequently validated in real-time quantitative polymerase chain reaction analysis in a mouse model of kainic acid-induced epilepsy. The expression patterns of nine genes were consistent with sequencing outcomes. Meanwhile, several genes, including CX3CR1, CX3CL1, GPR183, FPR1, P2RY13, P2RY12 and LPAR5, were associated with microglial activation and migration, providing novel candidate targets for immunotherapy in epilepsy and laying the foundation for further research.